Pengembangan Modul Berbasis Strategi REACT (Relating, Experiencing, Applying, Cooperating, and Transfering) Berbantuan Flipbook Maker Pada Materi Bangun Datar Kelas VII SMPN 2 Turatea - Nurul Fatimah; Andi Kusumayanti; Nursalam; Andi Ika Prasasti Abrar (Department of Mathematics Education, 2023)
This study aims to determine the process and results of module development based on the REACT strategy assisted by flipbook makers on class VII flat construction material that is valid, practical, and effective so that it is feasible to use. This type of research is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The results showed that the validity criteria based on the validation results by the validator team was 3.68 in the